PERLINDUNGAN HUKUM TERHADAP KEARSIPAN DI PENGADILAN NEGERI MEDAN SEBAGAI BAGIAN DARI INFORMASI PUBLIK - Sihaloho, Junico Darpindo; Nababan, Roida (Lembaga Dongan Dosen, 2025)
Archives are one of the important components in a court, including the Medan District Court. Based on Article 1 number 2 of the Republic of Indonesia Law Number 43 of 2009 concerning Archives, the definition of archives is